Communication, relationships and practices in virtual work - Long, Shawn; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This book provides exploration of the opportunities, benefits and costs associated with virtual work, addressing several communicative, relational and practical issues associated with virtual work"--Provided by publisher.
1. Examining tensions in telework policies / Jennifer Gibbs, Craig Scott, Young Kim, Sun Lee -- 2. Communication, structural links, and conflict in three inter-organizational virtual collaborations / Tyler Harrison, Elizabeth Williams -- 3. Online teaching as virtual work in the new (political) economy / Roy Schwartzman, David Carlone -- 4. The ethical implications of the virtual work environment / Rachel Byers -- 5. The electronic panopticon / Shawn Long, Richie Goodman, Chase Clow -- 6. Virtual team identity construction and boundary maintenance / Huiyan Zhang, Marshall Poole -- 7. Temporary virtual teams / Stacey Connaughton, Elizabeth Williams, Jennifer Linvill, Elizabeth O'Connor, Troy Hayes -- 8. Status and influence processes in virtual teams and mobile collaborations / Elizabeth Ravlin -- 9. Sense of community in professional virtual communities / Anita Blanchard, David Askay, Katherine Frear -- 10. Virtual mentoring / Narissra Punyanunt-Carter, Emilio Hernandez -- 11. Politics in virtual work / Shawn Long, Marla Boughton, Rachel Widener -- 12. The amplification of power dynamics in virtual work / Stephen Yungbluth, Zachary Hart -- 13. Engineers' perceptions of relational limitations intrinsic to virtual work / Eletra Gilchrist -- 14. Power and trust in the virtual workplace / Ardis Hanson, Eric Engel, Sheila Gobes-Ryan -- 15. Structuring a local virtual work ecology for a collaborative, multi-institutional higher educational project / Shalin Hai-Jew -- 16. Aided system of competence management for virtual team building adapted to specific needs of design projects / Marinita Schumacher, Julie Le Cardinal, Jean-Claude Bocquet.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Telecommuting; Virtual work; Dynamics of virtual teams; Virtual work environments; Organizational identity; Virtual mentoring; Power dynamics; Mobile collaboration; Human-computer interaction; Trust in virtual work; Surveillance in virtual work; Politics of virtual work; Electronic books